Systematization of the psychological practice in medical settings (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
The traditional practice and the non-directive work of psychologists in hospitals have prevented an adequate insertion of this professional in this setting because medicine is a science founded on evidence-based knowledge. To implement interdisciplinary work and produce better results for the patients it is necessary to organize the psychological work through systematic records and constant analysis of procedures and interventions. These are actions needed to support a scientific attitude of psychologists working in hospitals. However, the use of rigid research protocols not linked to clinical practice does not favor an adequate insertion. In this article, examples of systematization of interconsultation and psychological routine practices of a University Hospital (HCFMRPUSP) will be presented. Data from these systematized clinical interventions favored the interaction of the psychologist with the team, brought benefits in terms of patient care and produced knowledge that aided the construction of psychological science in the hospital setting.